2007
DOI: 10.1007/s11606-006-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving Death Certificate Completion: A Trial of Two Training Interventions

Abstract: The death certificate is an important medical document that impacts mortality statistics and health care policy. Resident physician accuracy in completing death certificates is poor. We assessed the impact of two educational interventions on the quality of death certificate completion by resident physicians. Two-hundred and nineteen internal medicine residents were asked to complete a cause of death statement using a sample case of in-hospital death. Participants were randomized into one of two educational int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 17 publications
0
72
0
4
Order By: Relevance
“…20 Other potential causes of this observed disparity include biological differences in the tumor and in male versus female patients, as well as the higher prevalence of hypertension in males versus females. 16 As with most studies, the findings of this study must be generalized with caution. Gaps in data completeness for staging and, to a much lesser extent, race/ethnicity may affect accuracy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…20 Other potential causes of this observed disparity include biological differences in the tumor and in male versus female patients, as well as the higher prevalence of hypertension in males versus females. 16 As with most studies, the findings of this study must be generalized with caution. Gaps in data completeness for staging and, to a much lesser extent, race/ethnicity may affect accuracy.…”
Section: Discussionmentioning
confidence: 83%
“…5 However, death certificate accuracy is often as low as 40% due to wording inaccuracies and lack of training among physicians. 16 Because of this and because 10% of the patients in this study did not even have a death certificate available, it was decided that the cause of death data was not an effective means for accounting for co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo 24 . No pré-teste, apenas 15% dos médicos do grupo 1 e 16% do grupo 2 identificaram corretamente a causa do óbito, perfazendo um total geral de 15,5% de adequação no preenchimento da DO.…”
Section: Acurácia Do Sim Na Seleção Da Causa Básicaunclassified
“…Similarly a study by Myers et al from Canada which implemented a 75-min seminar showed that the percent of certificates with at least one major error was dropped from 32.9 to 15.7%. While Lakkiredoly et al from USA revealed that a 45-min workshop enabled 15.5% of residents to identify correctly the cause of death (17). Concerning the minor errors in Afzal Azim et al, all pre intervention had no time intervals (100%) and use of abbreviation (89.3%) after intervention there was a statistically significant decrease to 22.6% and 29.3% respectively whereas in Myers et al the probability of finding at least one minor error did not change significantly after the intervention (18).…”
Section: Resultsmentioning
confidence: 99%